What constitutes the concept of law? Potentialism as a position beyond positivism and natural law theory - Kähler, Lorenz (Law and morals : proceedings of the Special Workshop held at the 28th World Congress of the International Association for Philosophy of Law and Social Philosophy in Lisbon, Portugal, 2017)
The dispute about the proper concept of law has long suggested that there is one concept of law that does not change with society or time. In this regard, positivism and natural law theory agree that there is a definite concept of law, although they disagree about its precise content. The paper examines this assumption by looking at the reasons that constitute the concept of law. It argues that this assumption of an unchangeable nature of the concept of law is implausible as normative reasons turn out to be decisive for this formation. The weight of these reasons might, at least, in principle depend on changing circumstances. The same holds if empirical circumstances are constitutive for the concept of law, because they might change as well. Consequently, the concept of law does not have an a priori fixed content. Instead, it takes on a mere potential relationship to morality. This paper outlines this theory of potentialism.